Polylactic acid nanofiber filtering membrane as well as preparation method and application thereof

Stereoform composite nanofiber membranes were prepared through spinning process and annealing treatment, and MOFs seeds were synthesized in situ on them. Combined with microwave treatment, the problems of insufficient strength and air filtration effect of existing degradable filter materials were solved, and the problem of insufficient air filtration effect was achieved. Efficient and low-cost air filtration effect.

CN119186276APending Publication Date: 2024-12-27SHENHUA SHENDONG COAL GRP +3
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411647937.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing degradable filter materials have low strength and poor air filtration effect, making it difficult to meet the needs of efficient air purification.

Method used

Two-component polylactic acid nanofibers were prepared by spinning technology, and a tacit composite nanofiber membrane was formed by annealing, and metal organic frames (MOFs) were synthesized in situ on it. Combined with microwave processing technology, high resistance was prepared Heat, functionalized polylactic acid nanofiber filter membrane.

Benefits of technology

The polylactic acid nanofiber filter membrane with high fracture strength, specific surface area and surface potential has been achieved, which significantly improves the PM2.5 filtration efficiency. It is suitable for high-efficiency and low-cost air filters, with high dust capacity and long-term filtration performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119186276A_ABST
    Figure CN119186276A_ABST
Patent Text Reader

Abstract

The invention provides a polylactic acid nanofiber filtering membrane as well as a preparation method and application thereof. The preparation method comprises the following steps: S1, carrying out a spinning process on poly-L-lactic acid and poly-D-lactic acid to obtain bi-component polylactic acid nanofibers; step S2, carrying out annealing treatment on the bi-component polylactic acid nanofiber to obtain a stereocomplex nanofiber membrane; s3, the stereocomplex nanofiber membrane is placed in a first solution, MOFs seed crystals are synthesized in situ, a polylactic acid fiber membrane loaded with the MOFs seed crystals is obtained, and the first solution contains first zinc salt and a first organic ligand; s4, the polylactic acid fiber membrane loaded with the MOFs crystal seeds is placed in a second solution to be subjected to microwave treatment, the polylactic acid nanofiber filter membrane is obtained, and the second solution contains second zinc salt, a second organic ligand and a surfactant. The MOFs functionalized degradable polylactic acid nanofiber filter membrane with high heat resistance, high dust holding capacity and high surface potential is prepared in the invention.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of fiber filtration membrane materials, and in particular to a polylactic acid nanofiber filtration membrane, a preparation method and application thereof. Background Art

[0002] In recent years, the development of efficient and degradable filter materials has become a new trend. Among them, biodegradable polylactic acid materials have broad application prospects in the field of air filtration due to their non-toxicity and harmlessness.

[0003] Metal-organic framework (MOFs) nanosheets composed of metal ions and organic ligands have attracted widespread attention due to their large specific surface area, chemical tunability, and biocompatibility. In addition, the polar functional groups and high potential of MOFs can also promote the electrostatic capture of PMs, making MOFs a promising candidate material in the field of air filtration. Generally, MOFs have a polyhedral structure, and the preparation of nanosheet structures is still a great challenge. Summary of the invention

[0004] The main purpose of the present invention is to provide a polylactic acid nanofiber filter membrane, a preparation method and application thereof, so as to solve the problems of low strength and poor air filtration effect of degradable filter materials in the prior art.

[0005] In order to achieve the above-mentioned purpose, according to one aspect of the present invention, a method for preparing a polylactic acid nanofiber filter membrane is provided, and the preparation method comprises: step S1, subjecting left-handed polylactic acid and right-handed polylactic acid to a spinning process to obtain a two-component polylactic acid nanofiber; step S2, annealing the two-component polylactic acid nanofiber to obtain a stereocomposite nanofiber membrane; step S3, placing the stereocomposite nanofiber membrane in a first solution to in-situ synthesize MOFs seeds to obtain a polylactic acid fiber membrane loaded with MOFs seeds, wherein the first solution contains a first zinc salt and a first organic ligand; step S4, placing the polylactic acid fiber membrane loaded with MOFs seeds in a second solution for microwave treatment to obtain a polylactic acid nanofiber filter membrane, wherein the second solution contains a second zinc salt, a second organic ligand and a surfactant.

[0006] Furthermore, the weight average molecular weight of the L-polylactic acid is 100,000-800,000, and the optical purity is >92%;

[0007] The weight average molecular weight of dextrorotatory polylactic acid is 50,000-400,000, and the optical purity is >92%;

[0008] The mass ratio of L-polylactic acid to D-polylactic acid is 3:2 to 1:1;

[0009] The average diameter of the bicomponent polylactic acid nanofibers is 100-2000nm.

[0010] Further, the annealing treatment temperature is 80-110°C and the time is 10-120min;

[0011] The device used for the annealing treatment is at least one of an oven or a hot press;

[0012] Preferably, when an oven is used for annealing, the temperature is raised to the annealing temperature at a rate of 2-10°C / min, and after the annealing time is reached, the material is cooled naturally or cooled at a cooling rate of 2-10°C / min;

[0013] Preferably, when a hot press is used for annealing, the temperature is raised to the annealing temperature at a rate of 2-5°C / min, and after the annealing time is reached, the temperature is cooled at a rate of 2-5°C / min; preferably, a pressure of 0.1-0.5Mpa is applied during the heat preservation stage of the annealing;

[0014] Preferably, the thickness of the stereocomposite nanofiber membrane is 10-200 μm.

[0015] Further, the first zinc salt and the second zinc salt are each independently selected from at least one of zinc nitrate, zinc chloride, zinc sulfate, and zinc acetate;

[0016] The concentrations of the first zinc salt and the second zinc salt are independently 0.01-2 mol / L;

[0017] The first organic ligand and the second organic ligand are each independently at least one of 2-methylimidazole and benzimidazole;

[0018] The molar ratio of the first organic ligand to the first zinc salt is 10:1-5:1.

[0019] Further, in step S3, the temperature of in-situ synthesis of MOFs seed crystals is 25-60° C. and the time is 1-24 h;

[0020] Preferably, the mass of the MOFs seeds in the polylactic acid fiber membrane loaded with MOFs seeds accounts for 1% to 6.2% of the mass of the polylactic acid fiber membrane loaded with MOFs seeds;

[0021] Preferably, the slurry obtained after in-situ synthesis of MOFs seeds is washed and dried to obtain a polylactic acid fiber membrane loaded with MOFs seeds; preferably, the drying temperature is 60-100° C. and the drying time is 12-24 h.

[0022] Further, the surfactant is any one or more of dodecyltrimethylammonium bromide, tetradecyltrimethylammonium bromide, hexadecyltrimethylammonium bromide and octadecyltrimethylammonium bromide;

[0023] The molar ratio of the second organic ligand, the second zinc salt and the surfactant is (90-50):(10-5):(2-0.5).

[0024] Furthermore, the microwave output power of the microwave treatment is 200-5000W.

[0025] The temperature of microwave treatment is 60-100°C and the time is 10-80 minutes.

[0026] Furthermore, the breaking strength of the polylactic acid nanofiber filtration membrane is 15.3MPa-20.6MPa, and the specific surface area is 165-306m 2 / g, the surface potential is 7.9kV~11.2kV, and the PM2.5 filtration efficiency is 94.7-99.9%.

[0027] According to another aspect of the present application, a polylactic acid nanofiber filter membrane is provided. The polylactic acid nanofiber filter membrane is prepared by any one of the above-mentioned methods for preparing a polylactic acid nanofiber filter membrane.

[0028] According to another aspect of the present application, there is provided an application of the above-mentioned polylactic acid nanofiber filter membrane in air purification.

[0029] By applying the technical solution of the present invention, the preparation method of the polylactic acid nanofiber filter membrane provided in the present application combines the spinning process with the annealing treatment to prepare a stereocomposite polylactic acid fiber membrane with a high melting point and uniform diameter, giving the fiber membrane high heat resistance, providing a large number of dense anchoring points for MOFs seeds, and combining microwave-assisted oriented growth of MOFs, a MOFs-functionalized degradable polylactic acid nanofiber filter membrane with high heat resistance, high dust holding capacity and high surface potential is simply and efficiently prepared, which can be used to prepare an air filter that effectively removes PMs, is highly selective and low-cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0031] Figure 1 A schematic process flow diagram of a method for preparing a polylactic acid nanofiber filtration membrane according to Example 1 of the present invention is shown.

[0032] Figure 2 The SEM image (2 μm) of the polylactic acid nanofiber filtration membrane according to Example 1 of the present invention is shown;

[0033] Figure 3The SEM image (20 μm) of the polylactic acid nanofiber filtration membrane according to Example 1 of the present invention is shown. DETAILED DESCRIPTION

[0034] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.

[0035] As analyzed in the background technology of this application, the existing technology has the problem that the strength of the degradable filter material is low and the air filtration effect is poor. In order to solve this problem, this application provides a polylactic acid nanofiber filter membrane, a preparation method and application thereof.

[0036] According to a typical embodiment of the present application, a method for preparing a polylactic acid nanofiber filter membrane is provided, and the preparation method comprises: step S1, subjecting left-handed polylactic acid and right-handed polylactic acid to a spinning process to obtain a two-component polylactic acid nanofiber; step S2, annealing the two-component polylactic acid nanofiber to an annealing treatment to obtain a stereocomposite nanofiber membrane; step S3, placing the stereocomposite nanofiber membrane in a first solution to in-situ synthesize MOFs seeds to obtain a polylactic acid fiber membrane loaded with MOFs seeds, wherein the first solution contains a first zinc salt and a first organic ligand; step S4, placing the polylactic acid fiber membrane loaded with MOFs seeds in a second solution for microwave treatment to obtain a polylactic acid nanofiber filter membrane, wherein the second solution contains a second zinc salt, a second organic ligand and a surfactant.

[0037] The preparation method of the polylactic acid nanofiber filter membrane provided in the present application combines the spinning process with the annealing treatment to prepare a stereocomposite polylactic acid fiber membrane with a high melting point and uniform diameter, giving the fiber membrane a high heat resistance property, providing a large number of dense anchoring points for MOFs seeds, and combining microwave-assisted oriented growth of MOFs, thereby simply and efficiently preparing a MOFs-functionalized degradable polylactic acid nanofiber filter membrane with high heat resistance, high dust holding capacity and high surface potential, which can be used to prepare an air filter that effectively removes PMs, is highly selective and low-cost.

[0038] The left-handed polylactic acid (PLLA) and right-handed polylactic acid (PDLA) used as raw materials can be selected from the existing technology. In order to further improve the performance of the polylactic acid nanofiber filtration membrane, the weight average molecular weight of the left-handed polylactic acid is preferably 100,000-800,000, and the optical purity is >92%; the weight average molecular weight of the right-handed polylactic acid is preferably 50,000-400,000, and the optical purity is >92%.

[0039] In some typical embodiments of the present application, the mass ratio of L-polylactic acid to D-polylactic acid is 3:2 to 1:1, which can better exert the synergistic effect of the two and further improve the performance of the polylactic acid nanofiber filtration membrane.

[0040] The spinning process can be selected from the prior art, such as solution spinning or melt spinning.

[0041] In some embodiments of the present application, the solution spinning method used in the above step S1 is at least one of coaxial electrospinning, parallel electrospinning technology, double needle electrospinning technology and single needle electrospinning technology, the voltage is 10-30kV, the temperature is 20-60°C, the humidity is 20-60%, the spinning solution consumption rate is 0.1-10mL / h, and the receiving distance is 10-25cm. Preferably, the solvent for dissolving polylactic acid in the solution spinning method is at least one of chloroform, acetone, ethyl acetate, dimethylformamide, ethanol, dichloromethane, and chloroform, and the mass concentration of left-handed polylactic acid and right-handed polylactic acid in the solution is independently 0.5-15wt%.

[0042] In some embodiments of the present application, the above-mentioned melt spinning method is at least one of spunbonding and meltblowing technology; preferably, the parameters of spunbonding include: the temperature of the melt preparation section is 170℃~220℃, the temperature of the melt filtration, metering and spinning section is 210℃~230℃, the cooling air temperature is <30℃, and the speed is 0.1~1m / s; preferably, the parameters of meltblowing include: the temperature of the melt preparation section is 170℃~230℃, the temperature of the melt filtration, metering and spinning section is 210℃~230℃, the air temperature is 220℃~240℃, and the speed is 0.1~1m / s.

[0043] In some embodiments of the present application, the average diameter of the above-mentioned two-component polylactic acid nanofibers prepared by step S1 is 100-2000 nm, and after annealing treatment, it is more conducive to the oriented growth of MOFs.

[0044] In the above step S2, by annealing the two-component polylactic acid nanofibers, a stereocomposite nanofiber membrane with a specific three-dimensional structure is induced to form. In some embodiments of the present application, the temperature of the annealing treatment is 80-110°C and the time is 10-120min, so that the stereocomposite nanofiber membrane obtained after the annealing treatment has better heat resistance and provides more anchoring points for MOFs seed crystals. Specifically, the temperature of the annealing treatment can be 80°C, 82°C, 84°C, 85°C, 86°C, 88°C, 90°C, 92°C, 94°C, 95°C, 97°C, 100°C, 102°C, 104°C, 105°C, 107°C, 109°C, etc., but is not limited to this. Specifically, the annealing time can be 10 min, 20 min, 30 min, 40 min, 50 min, 60 min, 70 min, 80 min, 90 min, 100 min, 110 min, 120 min, etc., and of course it can also be other values ​​within the above range.

[0045] In some typical embodiments of the present application, the device used for the annealing treatment is at least one of an oven and a hot press.

[0046] In order to further improve the effect of annealing treatment, when using an oven for annealing treatment, the temperature is raised to the annealing temperature at a rate of 2-10°C / minute. After reaching the annealing time, it is naturally cooled, or cooled at a cooling rate of 2-10°C / minute; when this annealing treatment method is adopted, the annealing temperature is preferably 80°C to 150°C, more preferably 80-110°C, and the time is 10-120min.

[0047] In some preferred embodiments of the present application, when a hot press is used for annealing, the temperature is increased to the annealing temperature at a rate of 2-5°C / min, and after the annealing time is reached, the temperature is cooled at a rate of 2-5°C / min, which can make the annealing effect better; preferably, a pressure of 0.1-0.5MPa is applied during the insulation stage of the annealing; when this annealing method is adopted, preferably, the annealing temperature is 80-110°C and the time is 0.1-2h.

[0048] In some embodiments of the present application, the thickness of the stereocomposite nanofiber membrane is 10-200 μm, which is convenient for the subsequent in-situ growth of MOFs seeds and the use of the finished product.

[0049] In step S3 and step S4, the first zinc salt and the second zinc salt and the first organic ligand and the second organic ligand used for in situ synthesis of MOFs can be selected from the prior art. For example, the first zinc salt and the second zinc salt are each independently selected from at least one of zinc nitrate, zinc chloride, zinc sulfate, and zinc acetate; the first organic ligand and the second organic ligand are each independently selected from at least one of 2-methylimidazole and benzimidazole.

[0050] In some embodiments of the present application, in step S3, the concentration of the first zinc salt is 0.01-2 mol / L, and the molar ratio of the first organic ligand to the first zinc salt is 10:1-5:1, which is conducive to the uniform growth of MOFs seeds on the surface of the stereocomposite nanofiber membrane.

[0051] In some typical embodiments of the present application, in step S3, the temperature of in-situ synthesis of MOFs seeds is 25-60°C, the time is 1-24h, and the formed MOFs seeds are relatively uniform and the particle size is relatively suitable. Preferably, the mass of MOFs seeds in the polylactic acid fiber membrane loaded with MOFs seeds accounts for 1% to 6.2% of the mass of the polylactic acid fiber membrane loaded with MOFs seeds, so that the MOFs seeds are subsequently converted into MOFs nanosheets through microwave assistance, and better interact with the stereocomposite nanofiber membrane to improve its filtration capacity.

[0052] In some preferred embodiments of the present application, the slurry obtained after in-situ synthesis of MOFs seeds is washed and dried to obtain a polylactic acid fiber membrane loaded with MOFs seeds. Through the drying process, the MOFs seeds can be firmly fixed on the surface and pores of the fiber membrane, increasing the adhesion between the MOFs seeds and the stereocomposite nanofiber membrane; and through the drying process, the residual solvent in the polylactic acid fiber membrane loaded with MOFs seeds can be removed to prevent the membrane structure from changing or the physical properties from decreasing due to the solution components during storage and use, thereby ensuring the structural stability of the filter membrane. Preferably, the drying temperature is 60-100°C and the time is 12-24h.

[0053] In the above step S4, the polylactic acid fiber membrane loaded with MOFs seeds is placed in the second solution, and under the auxiliary conditions of microwave treatment, the MOFs seeds are grown in situ in a confined space and converted into MOFs nanosheets. The polylactic acid nanofiber filtration membrane having the in situ grown MOFs nanosheets has the advantages of high strength, high specific surface area, high surface potential, high efficiency, low resistance and long-term filtration.

[0054] In some embodiments of the present application, the surfactant in the second solution is any one or more of dodecyltrimethylammonium bromide (DTAB), tetradecyltrimethylammonium bromide (TTAB), hexadecyltrimethylammonium bromide (CTAB) and octadecyltrimethylammonium bromide (STAB). The above surfactant can effectively prevent the aggregation or uneven growth of crystals on the surface of the polylactic acid fiber membrane, and can also reduce the surface tension, provide more active sites, and promote the nucleation and growth of MOFs seeds on the polylactic acid fiber.

[0055] In some preferred embodiments of the present application, the molar ratio of the second organic ligand, the second zinc salt and the surfactant is (90-50): (10-5): (2-0.5), wherein the concentration of the second zinc salt is 0.01-2 mol / L, which is conducive to the uniform and rapid growth of MOFs nanosheets.

[0056] In order to further improve the performance of the polylactic acid nanofiber filter membrane with MOFs nanosheets, in some embodiments of the present application, the temperature of the microwave treatment is 60-100°C and the time is 10-80 minutes. In some embodiments of the present application, the above step S4 is carried out in a microwave reactor, and the microwave output power of the microwave reactor is 200-5000W. At this microwave intensity, it is conducive to preparing a polylactic acid nanofiber filter membrane with better performance.

[0057] In some typical embodiments of the present application, the polylactic acid nanofiber filtration membrane prepared by the above method has a breaking strength of 15.3MPa-20.6MPa and a specific surface area of ​​165-306m 2 / g, the surface potential is 7.9kV~11.2kV, and the PM2.5 filtration efficiency is 94.7-99.9%. It is a filtration membrane with high strength, high specific surface area, high surface potential, high efficiency and low resistance, and long-term filtration.

[0058] According to another typical embodiment of the present application, a polylactic acid nanofiber filter membrane is provided. The polylactic acid nanofiber filter membrane is prepared by any one of the above-mentioned methods for preparing the polylactic acid nanofiber filter membrane.

[0059] The polylactic acid nanofiber filtration membrane of the present application utilizes the high heat resistance of stereocomposite polylactic acid, combined with green and efficient microwave-assisted synthesis technology, to achieve the restricted growth of MOFs nanosheets directly on the surface of polylactic acid nanofibers, giving the fiber membrane high surface activity, high interception efficiency, and high surface potential, making it have the characteristics of high efficiency, low resistance and full degradation.

[0060] According to another typical embodiment of the present application, an application of the above-mentioned polylactic acid nanofiber filter membrane in air purification is provided. Since the above-mentioned polylactic acid nanofiber filter membrane has the characteristics of high heat resistance, high dust holding capacity, high surface potential, and can be degraded, it has broad application prospects in air purification, and is particularly suitable for preparing air filters that are efficient in removing PMs, highly selective, and low-cost.

[0061] The beneficial effects that can be achieved by the present application will be further illustrated below in combination with embodiments and comparative examples.

[0062] Example 1

[0063] In-situ growth of MOFs nanosheet functionalized polylactic acid nanofiber filtration membrane and preparation method thereof, the process flow is as follows Figure 1 As shown, the following steps are included:

[0064] S11. Preparation of bicomponent polylactic acid nanofibers: PLLA (weight average molecular weight of 80W, optical purity>92%) and PDLA (weight average molecular weight of 40W, optical purity>92%) were dissolved in chloroform to obtain spinning solutions with a concentration of 0.5wt% each; PLLA was used as the inner spinning solution at a consumption rate of 0.1mL / h, PDLA was used as the outer spinning solution at a consumption rate of 0.1mL / h, the spinning voltage was 10kV, and tin foil was used as the receiving substrate to perform coaxial electrospinning to obtain bicomponent polylactic acid nanofibers with a skin-core structure (fiber diameter of 1236±16.2nm);

[0065] S12. Preparation of stereocomposite nanofiber membrane: The nanofiber obtained in step S11 was annealed in an oven, heated to 80°C at a rate of 5°C / min for 24 min, and cooled at a rate of 5°C / min to obtain a stereocomposite polylactic acid nanofiber membrane with a thickness of 12 μm;

[0066] S13. Preparation of PLA@MOFs nanofiber membrane: The polylactic acid nanofiber membrane prepared in step S12 was immersed in a mixed solution of zinc salt zinc acetate (0.01 mol / L), organic ligand 2-methylimidazole (the molar ratio of 2-methylimidazole to zinc acetate is 10:1) and water (25°C, 4h), washed, and dried at 60°C for 6h to obtain a polylactic acid fiber membrane (i.e., PLA@MOFs nanofiber membrane) with uniformly grown MOFs seeds, wherein the weight of the MOFs seeds is 4.5%±0.2% relative to the weight of the fiber membrane;

[0067] S14. Preparation of PLA@MOFs nanosheet stereocomposite fiber membrane: The PLA@MOFs nanofiber membrane prepared in S13 and a mixed solution containing zinc salt zinc acetate (0.01 mol / L), organic ligand 2-methylimidazole and surfactant CTAB (the molar ratio of 2-methylimidazole, zinc acetate and CTAB is 10:1:0.1) and water are placed in a microwave reactor (output power 500 W) to in situ grow MOFs sheets (60°C, 80 min). After the reaction, it is washed three times with deionized water to remove loosely bound MOFs crystals. The in situ modified polylactic acid fiber membrane is placed in an oven at 60°C and dried for 24 h to obtain an in situ grown MOFs nanosheet functionalized polylactic acid nanofiber filtration membrane, namely, a PLA@MOFs nanosheet stereocomposite fiber membrane.

[0068] The microstructure of the PLA@MOFs nanosheet stereocomposite fiber membrane is shown in Figure 2 and Figure 3 shown.

[0069] Example 2

[0070] In-situ growth of MOFs nanosheet functionalized polylactic acid nanofiber filtration membrane and preparation method thereof, comprising the following steps:

[0071] S21. Preparation of bicomponent polylactic acid nanofibers: PLLA (weight average molecular weight of 30W, optical purity>92%) and PDLA (weight average molecular weight of 20W, optical purity>92%) were dissolved in acetone to obtain spinning solutions with a concentration of 15wt% each; parallel electrospinning technology was used, the consumption rate of PLLA spinning solution and PDLA spinning solution was 10mL / h, the spinning voltage was 25kV, and tin foil was used as a receiving substrate for electrospinning to obtain bicomponent polylactic acid nanofibers (fiber diameter was 568±6.8nm);

[0072] S22. Preparation of stereocomposite polylactic acid nanofiber membrane: The nanofibers obtained in step S21 were annealed in an oven, heated to 100°C at a rate of 5°C / min for 60 min, and cooled at a rate of 5°C / min to obtain a stereocomposite polylactic acid nanofiber membrane with a thickness of 20 μm;

[0073] S23. Preparation of PLA@MOFs nanofiber membrane: The polylactic acid nanofiber membrane prepared in step S22 was immersed in a mixed solution of zinc acetate (2 mol / L) and 2-methylimidazole (the molar ratio of 2-methylimidazole to zinc acetate was 5:1) (40°C, 4h), washed, and dried at 60°C for 6h to obtain a polylactic acid fiber membrane with uniformly grown MOFs seeds, wherein the weight of the MOFs seeds was 5.3%±0.6% relative to the weight of the fiber membrane;

[0074] S24. Preparation of PLA@MOFs nanosheet stereocomposite fiber membrane: The mixed solution of polylactic acid fiber membrane containing MOFs seeds prepared in S23, zinc acetate (2 mol / L), 2-methylimidazole and DTAB (the molar ratio of 2-methylimidazole, zinc acetate and DTAB is 5:1:0.05) is placed in a microwave reactor (output power 500 W) to in situ grow MOFs sheets (100°C, 30 min). After the reaction, it is washed three times with deionized water to remove loosely bound MOFs crystals. Finally, the in situ modified polylactic acid fiber membrane is placed in an oven at 100°C and dried for 12 h to obtain an in situ grown MOFs nanosheet functionalized polylactic acid nanofiber filtration membrane.

[0075] Example 3

[0076] In-situ growth of MOFs nanosheet functionalized polylactic acid nanofiber filtration membrane and preparation method thereof, comprising the following steps:

[0077] S31. Preparation of bicomponent polylactic acid nanofibers: PLLA (weight average molecular weight of 60W, optical purity>92%) and PDLA (weight average molecular weight of 30W, optical purity>92%) were dissolved in chloroform to obtain spinning solutions with a concentration of 15wt% each; PDLA was used as the inner spinning solution at a consumption rate of 10mL / h, PLLA was used as the outer spinning solution at a consumption rate of 10mL / h, the spinning voltage was 25kV, and tin foil was used as the receiving substrate to perform coaxial electrospinning to obtain bicomponent polylactic acid nanofibers with a skin-core structure (fiber diameter of 523±6.8nm);

[0078] S32. Preparation of stereocomposite nanofiber membrane: The nanofiber obtained in step S31 was annealed in an oven, heated to 100°C at a rate of 5°C / min for 20min, and cooled at a rate of 5°C / min to obtain a stereocomposite polylactic acid nanofiber membrane having a thickness of 18 μm;

[0079] S33. Preparation of PLA@MOFs nanofiber membrane: Immerse the polylactic acid nanofiber membrane prepared in step S32 in a mixed solution of zinc chloride (1 mol / L) and 2-methylimidazole (the molar ratio of 2-methylimidazole to zinc acetate is 8:1) (40°C, 8h), wash, and dry at 60°C for 4h to obtain a polylactic acid fiber membrane with uniformly grown MOFs seeds, wherein the weight of the MOFs seeds is (6.2±0.6)% relative to the weight of the fiber membrane;

[0080] S34. Preparation of PLA@MOFs nanosheet stereocomposite fiber membrane: The mixed solution of polylactic acid fiber membrane containing MOFs seeds prepared in S33, zinc acetate (2 mol / L), 2-methylimidazole, and DTAB (the molar ratio of 2-methylimidazole, zinc acetate and DTAB is 8:1:0.1) are placed in a microwave reactor (output power 800 W) to in situ grow MOFs sheets (80°C, 1 h). After the reaction, it is washed three times with deionized water to remove loosely bound MOFs crystals. Finally, the in situ modified polylactic acid fiber membrane is placed in an oven at 100°C and dried for 12 h to obtain an in situ grown MOFs nanosheet functionalized polylactic acid nanofiber filtration membrane.

[0081] Example 4

[0082] In-situ growth of MOFs nanosheet functionalized polylactic acid nanofiber filtration membrane and preparation method thereof, comprising the following steps:

[0083] S41. Preparation of bicomponent polylactic acid nanofibers: Preparation of polylactic acid composite fiber membrane by melt spinning, wherein the weight average molecular weight of PLLA is 60W, the optical purity is >92%, the weight average molecular weight of PDLA is 30W, the optical purity is >92%, and the mass ratio of PLLA to PDLA is 1:1; the temperature of the melt preparation section is 190°C, the temperature of the melt filtration, metering, and spinning section is 220°C, the cooling air temperature is 25°C, and the speed is 0.5m / s;

[0084] S42. Preparation of a stereocomposite nanofiber membrane: The nanofibers obtained in step S41 were annealed using a hot press, heated to 100°C at a rate of 2°C / min and maintained for 15 min, during which the pressure was 0.5 MPa, and cooled at a rate of 2°C / min to obtain a stereocomposite polylactic acid nanofiber membrane having a thickness of 168 μm;

[0085] S43. Preparation of PLA@MOFs nanofiber membrane: The polylactic acid nanofiber membrane prepared in step S42 was immersed in a mixed solution of zinc nitrate (0.02 mol / L) and benzimidazole (the molar ratio of benzimidazole to zinc nitrate was 6:1) (50°C, 3h), washed, and dried at 60°C for 4h to obtain a polylactic acid fiber membrane with uniformly grown MOFs seeds, wherein the weight of the MOFs seeds was (4.3±0.6)% relative to the weight of the fiber membrane;

[0086] S44. Preparation of PLA@MOFs nanosheet stereocomposite fiber membrane: The mixed solution of polylactic acid fiber membrane containing MOFs seeds prepared in S43, zinc nitrate (0.02 mol / L), benzimidazole, and DTAB (the molar ratio of benzimidazole, zinc nitrate and DTAB is 6:1:0.1) is placed in a microwave reactor (output power 800 W) to in situ grow MOFs sheets (80°C, 30 min). After the reaction, it is washed three times with deionized water to remove loosely bound MOFs crystals. Finally, the in situ modified polylactic acid fiber membrane is placed in an oven at 100°C and dried for 12 h to obtain an in situ grown MOFs nanosheet functionalized polylactic acid nanofiber filtration membrane.

[0087] Example 5

[0088] The difference from Example 1 is that in step S13, the immersion time of the polylactic acid nanofiber membrane in the mixed solution is 12 hours, and the mass content of MOFs seeds in the prepared polylactic acid fiber membrane with uniformly grown MOFs seeds is 7%.

[0089] Example 6

[0090] The difference from Example 1 is that in step S14, the temperature for in-situ growth of MOFs sheets in the microwave reactor is 100° C. and the time is 80 minutes.

[0091] Example 7

[0092] The difference from Example 1 is that in step S14, the temperature for in-situ growth of the MOFs sheet in the microwave reactor is 50° C. and the time is 80 minutes.

[0093] Example 8

[0094] The difference from Example 1 is that in step S12, the temperature is raised to the annealing temperature (100° C.) within 15 minutes during annealing.

[0095] Comparative Example 1

[0096] The difference from Example 1 is that: in step S14, the fiber membrane containing MOFs seeds prepared in step S13 is immersed in a mixed solution of zinc acetate (0.01 mol / L), 2-methylimidazole, and DTAB (the molar ratio of 2-methylimidazole, zinc acetate and DTAB is 10:1:0.1), and placed in a hydrothermal reactor to in situ grow MOFs sheets (60°C, 80 min). After the reaction is completed, it is washed three times with deionized water to remove loosely bound MOFs crystals. Finally, the in situ modified polylactic acid fiber membrane is placed in a 60°C oven and dried for 24 hours to obtain an in situ MOF-modified polylactic acid nanofiber filtration membrane.

[0097] Comparative Example 2

[0098] The difference from Example 2 is that step S22 is not performed, and the bicomponent polylactic acid nanofibers prepared in step S21 are directly used in step S23 by immersing them in the mixed solution.

[0099] The polylactic acid nanofiber filtration membranes prepared in the above examples and comparative examples were subjected to structural characterization and performance testing according to the following methods. The test results are listed in Table 1 below.

[0100] Specific surface area test The nitrogen adsorption isotherms were measured at 77 K using a gas adsorption instrument (ASAP 2060, Micromeritics, USA).

[0101] Thermal performance test :The thermal properties of the obtained fiber membrane were analyzed using a DSC-6200 differential scanning calorimeter (DSC) from Perkin Elmer, USA. 3-5 mg of sample powder was placed in a crucible and pressed tightly. Nitrogen protection was used during the test, with a gas flow rate of 50 mL / min, a heating rate of 20°C / min, and a heating range of 30-250°C.

[0102] Tensile properties test :The obtained fiber film was cut to obtain tensile specimens, and the tensile properties of the composite material were tested using a universal tensile machine (model 4403, sensor 100N) of Instron Company of the United States according to the ASTM D638-2003 plastic tensile properties test standard of the American Society for Testing and Materials. At least 3 parallel test samples were guaranteed for each group, and the results were averaged.

[0103] Surface potential test The surface potential of the nanofiber membrane was tested using a non-contact electrostatic meter (VM54XQS, Quatek, USA). The test height was 2 cm, the temperature and humidity were constant at 25°C and 45%, and 20 data points were randomly collected for each sample and the average value was taken.

[0104] Filtration performance test:The fiber membrane (area 113.04cm 2 ) air filtration performance, the gas flow rate was set to 85L / min, and the particle size range of NaCl atomized particles produced by the aerosol generator was 0.1-10μm. At least 3 different positions of each group of fiber membranes were tested, and the results were averaged.

[0105] Dust holding capacity performance test :Under the above filtration conditions, after continuous filtration for 24 hours, the fiber membrane was taken out and weighed, and the dust holding capacity (DHC) of the filter material was calculated as follows. DHC = (M1-M0) / A, where M1 is the mass of the fiber membrane after the dust holding test, g; M0 is the mass of the unfiltered fiber membrane, g; A is the effective filtration area, 113.04 cm 2 .

[0106] Table 1

[0107]

[0108] Table 2

[0109]

[0110]

[0111] Table 1 compares the specific surface area, mechanical properties and filtration performance test results of the MOFs / PLA composite materials obtained in the examples and comparative examples. Examples 1-4 have higher specific surface areas (150.2-236.4 m 2 / g), although the specific surface areas of Examples 5-8 are relatively low, especially Example 6 (267.5 m 2 / g) and Example 8 (298.3m 2 / g), but compared with comparative examples 1-2, it can provide more active sites, greatly increase the roughness of the fiber surface, and thus effectively improve the mechanical filtration performance.

[0112] Examples 1-4 all have relatively high fracture strength (15.3MPa-20.6MPa), and the fracture strength of Examples 5-8 is in a relatively low range (5.7-14.4MPa), which reflects excellent mechanical properties and fully meets the mechanical property requirements of polylactic acid fiber membrane in the field of filtration materials. However, the fracture strength of Examples 1 and 2 is only 10.3MPa and 9.8MPa, which is mainly caused by uneven loading of MOFs crystals and softening of fibers.

[0113] It is also of great significance that Examples 1-4 all exhibit extremely high surface potentials (7.9kV to 11.2kV), and almost no attenuation occurs over time, confirming extremely high long-term stability. In particular, the initial value of the surface potential of Example 1 is as high as 11.2kV, which is 22 times that of Comparative Example 1 and nearly 5 times that of Comparative Example 2; and after 30 days, the surface potential of Example 1 is still maintained at 11.0kV. The surface potentials of Examples 5-8 are relatively low (4.6-8.2kV), indicating that their electrostatic adsorption performance is relatively weak. The surface potentials of Comparative Example 1 (6.8kV) and Comparative Example 2 (0.5kV) are relatively low and vary greatly over time, which directly affects their long-term filtration performance.

[0114] The loading amount of MOFs crystals and the temperature and time of microwave-assisted reaction are closely related to the surface potential and filtration performance of the polylactic acid membrane. Example 1 with the highest surface potential performs best in the filtration test. 0.3 and PM 2.5 The filtration efficiency reached 99.6% and 99.9% respectively, which is much higher than that of the comparative example 1-2 (PM 0.3 and PM 2.5 The filtration efficiency of Examples 5-8 gradually decreased. The filtration efficiency of Examples 5 and 6 for PM0.3 was 95.6% and 92.3%, and for PM2.5 was 92.3% and 93.4%, while the efficiency of Examples 7 and 8 was lower, especially for PM0.3, which dropped to 91.6%-93.4%.

[0115] Table 2 compares the dust holding capacity and thermal performance test results of the MOFs / PLA composite materials obtained in the examples and comparative examples. Examples 1-4 have higher dust holding capacity and can reach the maximum capacity (12.78 g / m 2 ), which is twice its own weight, especially Example 2 (12.78 g / m 2 ) and Example 3 (10.95 g / m 2 ) has a significantly higher dust holding capacity, which confirms that the stacking space formed by MOFs nanosheets is used to accommodate particulate matter, thereby increasing the dust holding capacity of the fiber membrane. The formation of stereocomposite crystals further improves the heat resistance of the fiber membrane, providing a more stable anchor point for the growth of nanosheets, promoting their restricted growth, and increasing the dust holding capacity of the fiber membrane.

[0116] The dust holding capacity of Examples 5-8 is relatively low, especially Example 6 (7.63 g / m 2 ) and Example 7 (7.51 g / m 2 ), which may cause more filtration blockage over a longer period of time. 2 ) and Comparative Example 2 (5.96 g / m 2) has a significantly lower dust holding capacity, which affects its effectiveness in actual use.

[0117] The increase in melting temperature and glass transition temperature is closely related to the crystallinity, molecular structure and presence of MOFs. The introduction of MOFs not only improves the crystallinity of the composite film, but also promotes the improvement of its thermal performance by stabilizing the growth of nanosheets. The thermal performance advantages of these materials enable them to maintain structural stability at higher temperatures and adapt to more complex working environments.

[0118] This shows that the polylactic acid fiber filtration membrane prepared by the preparation method of the present application makes the MOFs crystals have good surface properties and structural regularity, realizes the direct growth of MOFs nanosheets on the surface of polylactic acid nanofibers, and the MOFs / polylactic acid composite material obtains high surface potential and high filtration performance. These are likely due to: (1) the use of stereocomplexed polylactic acid nanofibers to achieve high heat resistance and increase MOFs loading and adhesion strength; (2) the use of green and efficient microwave-assisted synthesis technology to achieve secondary growth of MOFs nanosheets on the surface of polylactic acid nanofibers; (3) by loading MOFs sheets on the fiber surface, it is beneficial to maintain the high surface potential and high specific surface area of ​​the fiber membrane, achieve high dust holding capacity and long-term filtration, and expand the application prospects of polylactic acid fiber membranes.

[0119] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a polylactic acid nanofiber filter membrane, characterized in that: include: Step S1, spinning left-handed polylactic acid and right-handed polylactic acid to obtain bicomponent polylactic acid nanofibers; Step S2, annealing the bicomponent polylactic acid nanofibers to obtain a stereocomposite nanofiber membrane; Step S3, placing the stereocomposite nanofiber membrane in a first solution to in-situ synthesize MOFs seeds to obtain a polylactic acid fiber membrane loaded with MOFs seeds, wherein the first solution contains a first zinc salt and a first organic ligand; Step S4, placing the polylactic acid fiber membrane loaded with MOFs crystal seeds in a second solution for microwave treatment to obtain the polylactic acid nanofiber filtration membrane, wherein the second solution contains a second zinc salt, a second organic ligand and a surfactant.

2. The method for preparing the polylactic acid nanofiber filtration membrane according to claim 1, characterized in that: The weight average molecular weight of the L-polylactic acid is 100,000-800,000, and the optical purity is >92%; The weight average molecular weight of the dextrorotatory polylactic acid is 50,000-400,000, and the optical purity is >92%; The mass ratio of the L-polylactic acid to the D-polylactic acid is 3:2 to 1:1; The average diameter of the bicomponent polylactic acid nanofibers is 100-2000 nm.

3. The method for preparing the polylactic acid nanofiber filtration membrane according to claim 1, characterized in that: The annealing treatment is performed at a temperature of 80-110°C and a time of 10-120 minutes; The device used for the annealing treatment is at least one of an oven or a hot press; Preferably, when an oven is used for the annealing treatment, the temperature is raised to the annealing temperature at a rate of 2-10°C / min, and after the annealing time is reached, the annealing temperature is naturally cooled, or the annealing temperature is cooled at a rate of 2-10°C / min; Preferably, when a hot press is used for the annealing treatment, the temperature is raised to the annealing temperature at a rate of 2-5°C / min, and after the annealing time is reached, the temperature is cooled at a rate of 2-5°C / min; preferably, a pressure of 0.1-0.5Mpa is applied during the heat preservation stage of the annealing treatment; Preferably, the thickness of the stereocomposite nanofiber membrane is 10-200 μm.

4. The method for preparing the polylactic acid nanofiber filtration membrane according to claim 1, characterized in that: The first zinc salt and the second zinc salt are each independently selected from at least one of zinc nitrate, zinc chloride, zinc sulfate, and zinc acetate; The concentrations of the first zinc salt and the second zinc salt are independently 0.01-2 mol / L; The first organic ligand and the second organic ligand are each independently at least one of 2-methylimidazole and benzimidazole; The molar ratio of the first organic ligand to the first zinc salt is 10:1-5:

1.

5. The method for preparing the polylactic acid nanofiber filtration membrane according to claim 1 or 4, characterized in that: In step S3, the temperature for in-situ synthesis of MOFs seed crystals is 25-60° C. and the time is 1-24 h; Preferably, the mass of the MOFs seeds in the polylactic acid fiber membrane loaded with MOFs seeds accounts for 1% to 6.2% of the mass of the polylactic acid fiber membrane loaded with MOFs seeds; Preferably, the slurry obtained after in-situ synthesis of MOFs seeds is washed and dried to obtain the polylactic acid fiber membrane loaded with MOFs seeds; preferably, the drying temperature is 60-100° C. and the drying time is 12-24 h.

6. The method for preparing the polylactic acid nanofiber filtration membrane according to claim 1 or 4, characterized in that: The surfactant is any one or more of dodecyltrimethylammonium bromide, tetradecyltrimethylammonium bromide, hexadecyltrimethylammonium bromide and octadecyltrimethylammonium bromide; The molar ratio of the second organic ligand, the second zinc salt and the surfactant is (90-50): (10-5): (2-0.5).

7. The method for preparing the polylactic acid nanofiber filtration membrane according to claim 1 or 4, characterized in that: The microwave output power of the microwave treatment is 200-5000W, The temperature of the microwave treatment is 60-100° C., and the time is 10-80 minutes.

8. The method for preparing the polylactic acid nanofiber filtration membrane according to claim 1, characterized in that: The polylactic acid nanofiber filtration membrane has a breaking strength of 15.3MPa-20.6MPa and a specific surface area of ​​165-306m 2 / g, the surface potential is 7.9kV~11.2kV, and the PM2.5 filtration efficiency is 94.7-99.9%.

9. A polylactic acid nanofiber filtration membrane, characterized in that: The polylactic acid nanofiber filtration membrane is prepared by the preparation method of any one of claims 1 to 8.

10. Use of the polylactic acid nanofiber filter membrane according to claim 9 in air purification.

Citation Information

Cited By

  • High-porosity corrosion-resistant fiber membrane with armored structure as well as preparation method and application of high-porosity corrosion-resistant fiber membrane

    CN119663540A

  • A high-porosity corrosion-resistant armoring structure fiber membrane and a preparation method and application thereof

    CN119663540B